Brachial-ankle pulse wave velocity and mean platelet volume as predictive values after percutaneous coronary intervention for long-term clinical outcomes in Korea: A comparable and additive study. (3rd October 2015) - Seo, Hong-Joo; Ki, Young-Jae; Han, Mi Ah; Choi, Dong-Hyun; Ryu, Sang-Wan
Abstract: This study aimed to determine the association of the brachial-ankle pulse wave velocity (baPWV) and mean platelet volume (MPV) with the development of adverse outcomes after percutaneous coronary intervention (PCI). The baPWV and MPV were analyzed in 372 patients who underwent PCI, with the primary endpoint as cardiac death. The secondary endpoint was cardiovascular events (CVE): a composite of cardiac death, myocardial infarction (MI), target vessel revascularization (TVR), ischemic stroke, and stent thrombosis (ST). During the follow-up period (mean, 25.8 months), there were 21 cardiac deaths, 10 MIs including four events of ST, seven ischemic strokes, and 29 TVRs. The baPWV cut-off level was set at 1672 cm/s using the receiver operating characteristic curve; the sensitivity and specificity was 85.7 and 60.1%, respectively, to differentiate between the groups with and without cardiac death. The MPV cut-off level was set at 8.20 fL using the receiver operating characteristic curve; the sensitivity and specificity were 81 and 53.3%, respectively, to differentiate between the groups with and without cardiac death. Kaplan–Meier analysis revealed that the higher baPWV group (≥1672 cm/s) had a significantly higher cardiac death and CVE rate than the lower baPWV group (<1672 cm/s) (11.4 vs. 1.4%, log-rank: p < 0.0001; 25.3 vs. 7.5%, log-rank: p < 0.0001; respectively), and the higher MPV group (median, >8.20 fL, ) had a significantly higher cardiac death and CVE rate than the lower MPV group (≤8.20 fL) (9.4 vs. 2.1%, log-rank: p = 0.0026; 23.8 vs. 6.8%, log-rank: p < 0.0001; respectively). Furthermore, the high baPWV and MPV groups were significantly associated with an increased risk of cardiac death. These results show that baPWV and MPV are predictive markers after PCI for cardiac death; they are also additively associated with a higher risk of cardiac death.